1990
DOI: 10.1016/1010-7940(90)90166-w
|View full text |Cite
|
Sign up to set email alerts
|

Anatomically guided surgery to the AV node *1AV nodal skeletonization: experience in 46 patients with AV nodal reentrant tachycardia

Abstract: We report our combined experience with operative therapy for atrioventricular nodal tachycardia using an anatomically guided procedure. The operative rationale was to dissect the AV node with the intent of modifying perinodal tissues (skeletonization). The anterior septal and posterior septal regions were initially approached epicardially to facilitate endocardial dissection. Under normothermic cardiopulmonary bypass, the right atrial septum was mobilized and the intermediate AV node was exposed anterior to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The earliest attempts at nonpharmacologic cure of AVNRT involved surgical dissection in Koch's triangle. This technique was first introduced by Ross et al, 33 and the results were confirmed by a number of surgical groups 34–36 . Not only did the surgical reports pioneer non‐pharmacologic therapy but an impressive array of physiologic data was discovered.…”
Section: Surgical and Catheter Ablation Of Avnrtmentioning
confidence: 98%
See 1 more Smart Citation
“…The earliest attempts at nonpharmacologic cure of AVNRT involved surgical dissection in Koch's triangle. This technique was first introduced by Ross et al, 33 and the results were confirmed by a number of surgical groups 34–36 . Not only did the surgical reports pioneer non‐pharmacologic therapy but an impressive array of physiologic data was discovered.…”
Section: Surgical and Catheter Ablation Of Avnrtmentioning
confidence: 98%
“…This technique was first introduced by Ross et al, 33 and the results were confirmed by a number of surgical groups. [34][35][36] Not only did the surgical reports pioneer nonpharmacologic therapy but an impressive array of physiologic data was discovered. For example, high resolution mapping of Koch's triangle showed two distinct types of atrionodal connections in patients with "typical" slow-fast AVNRT.…”
Section: Surgical and Catheter Ablation Of Avnrtmentioning
confidence: 99%